The Internalization of Pancasila Values through Ethics and Character Education of Nations (Balinese Social-Cultural Perspective) - Pande Wayan Renawati (Universitas Sebelas Maret, 2021)
Indonesia is a country with a massive cultural diversity in every region. The cultural community certainly has its own characteristics to show their respective traditions with the natural forces of the region both real (sekala) and intangible (niskala). In that case, to live the socio -cultural life is certainly not independent of the procedures, attitudes and ethics when dealing with society. now, ethical attitudes in character seem almost extinct and neglected. This is becoming more viral with the participation of unethical attitudes by young people through youtube content, InstaGram, and other electronic media that have been rapidly developing lately. So it is necessary the role of parents, the role of educators, and the role of the government to be able to filter the food on the media and always direct the students to always improve the values of Pancasila as the basis of being ethical as a moral teaching. In this case, Pancasila will be discussed through ethical education from the point of view of Balinese Theology and Culture.